2008
DOI: 10.7205/milmed.173.3.230
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance during Military Deployment

Abstract: This preliminary investigation evaluated symptoms of sleep disturbance and insomnia in a group of 156 deployed military personnel. A 21-item Military Deployment Survey of Sleep was administered to provide self-reported estimates of a variety of sleep parameters. The results indicated that 74% of participants rated their quality of sleep as significantly worse in the deployed environment, 40% had a sleep efficiency of < 85%, and 42% had a sleep onset latency of > 30 minutes. Night-shift workers had significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(95 citation statements)
references
References 52 publications
5
88
1
1
Order By: Relevance
“…In stark contrast to mental health concerns, soldiers appear willing to seek help for sleep-related problems. Sleep problems are also common among active-duty military, especially while deployed (Peterson et al, 2008). The current findings converge with recent treatment trials showing that brief behavioral interventions for insomnia are associated with decreased depressive symptoms and suicidality post-treatment (Buysse et al, 2011;Manber et al, 2008, in submission;Morin et al, 2006Morin et al, , 2009; NIH Consensus Science Statements).…”
Section: Discussionsupporting
confidence: 81%
“…In stark contrast to mental health concerns, soldiers appear willing to seek help for sleep-related problems. Sleep problems are also common among active-duty military, especially while deployed (Peterson et al, 2008). The current findings converge with recent treatment trials showing that brief behavioral interventions for insomnia are associated with decreased depressive symptoms and suicidality post-treatment (Buysse et al, 2011;Manber et al, 2008, in submission;Morin et al, 2006Morin et al, , 2009; NIH Consensus Science Statements).…”
Section: Discussionsupporting
confidence: 81%
“…Finally, and particularly relevant for service members deployed to combat, a study assessing sleep disturbances in a deployed environment (Peterson, Goodie, Satterfield, & Brim, 2008) found approximately 75% of study participants rated their quality of sleep significantly worse than before deployment. In this study, sleep efficiency and sleep onset latency were in the range indicating insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disturbance and nightmares are two symptoms that constitute the diagnostic criteria for PTSD [3], and a substantial body of literature has documented sleep difficulties associated with this disorder [4][5][6][7]. For example, a recent study of 156 active-duty U.S. Air Force personnel deployed in Southwest Asia in support of OEF found that 74% reported poor sleep, with the most pronounced difficulties being sleep-onset latency and poor sleep efficiency [8]. Military personnel may continue to experience sleep difficulties after returning from their deployments, particularly if they develop symptoms of PTSD [9][10][11].…”
Section: Introductionmentioning
confidence: 99%